Analysis of Expert System Implementation in Computer Damage Diagnosis with Forward Chaining Method - Muhammad Rehan Anwar (Pandawan Sejahtera Indonesia, 2023)
The necessity for computerization is currently growing quickly because computers are now necessary for all needs connected to business and daily life. Therefore, users' ability to quickly and easily access information seems to be hindered by maintenance and repairs. An expert system is a computer-based method that uses facts, knowledge, and reasoning to solve issues that are often best handled by a subject-matter expert. Expert systems are created for expertise that is close to human capabilities in a given sector. A computer expert currently needs a lot of time to diagnose computer damage, and even technicians frequently put off their work in order to come up with fixes. Forward chaining was used in the construction of this system. In order to derive conclusions, forward chaining is employed to test the given factors against the recorded rules in the system. As a result, this expert system was developed to assist users in dealing with the damage and early maintenance that frequently affect computer systems. using computers in everyday tasks.If we are familiar with the Forward Chaining method used by the expert system to trace computer damage, the known crash features to address frequent crashes on that PC, and the application in object-oriented programming languages such as Visual Basic 6.0, we can determine where the damage is located.